Implementation Of Financing System at PT. BSI KCP Unismuh In Makassar - Azure (Pustaka Digital Indonesia, 2021)
The type of research conducted in this research is descriptive research with a qualitative approach. This type of descriptive research is research that tries to present facts objectively according to the conditions found when conducting research. The location of this research was carried out in the city of Makassar, precisely at PT. Indonesian Islamic Bank KCP Muhammadiyah University Makassar. The process in this research is starting from outlining, collecting, managing and analyzing data that is able to describe how the mechanism of the financing system at PT. Indonesian Islamic Bank KCP Unismuh in Makassar. From the results of the research conducted, it is concluded that for each financing product at BSI KCP UNISMUH Makassar before being offered to the customer, it has gone through screening and supervision by the sharia supervisory board and has been confirmed to be in accordance with Islamic sharia. The financing referred to here is the financing of Mutiguna, pension, OTO, Griya, Pawn Gold, and Installment Gold. From the informants, it was found that the mechanism used by BSI KCP UNISMUH Makassar was in accordance with theory and practice